Delayed atrophy in posterior cingulate cortex and apathy after stroke. (5th August 2014) - Matsuoka, Kiwamu; Yasuno, Fumihiko; Taguchi, Akihiko; Yamamoto, Akihide; Kajimoto, Katsufumi; Kazui, Hiroaki; Kudo, Takashi; Sekiyama, Atsuo; Kitamura, Soichiro; Kiuchi, Kuniaki; Kosaka, Jun; Kishimoto, Toshifumi; et al.
<x xml:space="preserve">Abstract</x> Objective A few studies have been performed on chronic structural changes after stroke. The primary purpose of the present study was to investigate regional cortical volume changes after the onset of stroke and to examine how the cortical volume changes affected neuropsychiatric symptoms. Methods Participants were 20 stroke patients and 14 control subjects. T1‐MRI was performed twice, once at the subacute stage and again 6 months later, and whole brain voxel‐based morphometric (VBM) analysis was used to detect significant cortical gray matter volume changes in patients. We also assessed the correlation between changes in cortical volumes and changes in neuropsychiatric symptoms during the 6 months following a stroke. Results In the present study, we found significant volume reductions in the anterior part of the posterior cingulate cortex (PCC) over the 6 months following a stroke by exploratory VBM analysis. We also found that the amount of volume change was significantly correlated with the change in apathy‐scale scores during the 6 months poststroke. Conclusions The present study suggests that delayed atrophic change is evident in the PCC 6 months after a stroke. There was greater apathetic change in the stroke patients with the larger volume reductions. The delayed atrophy of the PCC may reflect degeneration secondary to neuronal loss due to stroke. Such degeneration might have impaired control of goal‐directed behavior, leading to the observed increase in apathy. Copyright © 2014 John Wiley & Sons, Ltd.